A case report of a patient with bulky uterine cervical neoplasm who achieved complete response with "intentional internal high-dose policy" high-dose-rate interstitial brachytherapy. Issue 27 (2nd July 2020) - Kashihara, Tairo; Kobayashi, Kazuma; Iijima, Kotaro; Murakami, Naoya; Yoshida, Ken; Okuma, Kae; Nakamura, Satoshi; Takahashi, Kana; Inaba, Koji; Igaki, Hiroshi; Nakayama, Yuko; Kato, Tomoyasu; et al.
Abstract: Rationale: Gynecological high-dose-rate (HDR) brachytherapy has progressed for years, but it remains difficult for bulky tumors to be controlled locally. Dose limitations to organs at risk (OARs) are invariably obstacles in increasing the prescription dose. Additionally, it is controversial that the excessive hyperdose sleeve, the volume receiving a dose equal to or greater than twice the reference dose, should be eliminated in gynecological HDR brachytherapy. On the other hand, the technique of simultaneous integrated protection was reported for large hepatocellular carcinoma treatment, and similarly, internal high-dose brachytherapy could be used for treating bulky cervical carcinoma. Patient Concerns: A 54-year-old female had irregular genital bleeding and lost 13 kg in one year. Diagnosis: She was diagnosed with T3bN1M0 cervical cancer in another hospital. The transverse diameter of the primary tumor was 10.5 cm. Interventions: The whole pelvis and para-aortic lymph node were irradiated with a total of 50 Gy in 25 fractions, but the size of the tumor showed only a slight decrease to 8.9 cm. After external beam radiotherapy, first-time high-dose-rate interstitial brachytherapy (HDR-ISBT) was administered without "intentional internal high-dose (IIHD) policy, " the technique of high-dose administration to only the inside of the tumor. Considering the rectum dose limitation, in the additional 2 times of brachytherapy, "IIHD policy" HDR-ISBT was applied. In the second and third HDR-ISBT, the percentage of the volume exposed to 200% of the prescribed dose for high-risk clinical target volume increased by 241% and 204% compared with the first HDR-ISBT, while the doses to OARs were not significantly higher than those of the first-time HDR-ISBT. Outcomes: Complete response was obtained, and no recurrence findings and side effects caused by HDR-ISBT have been detected for 2 years and 9 months. Lessons: To our knowledge, this is the first report of IIHD HDR-ISBT for bulky cervical cancer. This technique can be the solution for treating bulky cervical cancer.